Facing Moral Crisis: Character Education Strategies for Millennials and Gen Z in Surakarta City - Ria Kasanova; Mohammad Rudiyanto; Anri Nofitria (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
The moral crisis plaguing the Millennial and Gen Z generations in Surakarta City shows complexity and escalation that requires serious attention. This article identifies and analyzes the main moral challenges faced by the younger generation, including the increase in bullying cases, the negative impact of social media, and the shift in social values in contemporary society. Through qualitative and quantitative approaches, this study explores the importance of character education as a strategic solution in responding to this crisis. Case studies from several schools in Surakarta show that the implementation of a holistic and integrated character education program can have a significant positive impact. The use of technology in character learning, the implementation of a value-based curriculum, and teacher training and development are the main pillars in this strategy. In addition, active involvement of parents and support from the local community also play an important role in shaping strong character and morals in the younger generation. This article contributes to the theory and practice of character education by highlighting the best practices that can be applied in addressing the moral crisis in Surakarta City. The practical implication is that a joint effort from all education and community stakeholders is needed to maintain the moral integrity of future generations. With the implementation of the right strategy and strong commitment, it is expected to build a solid moral foundation for the Millennial and Gen Z generations, creating a more just, harmonious and ethical society in Surakarta City.